PELAKSANAAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM TERKAIT DENGAN REKRUTMEN CALON LEGISLATIF OLEH PARTAI POLITIK DI KABUPATEN SUKOHARJO - Fahriyani, Irma Dwi; Suranto, Suranto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study aims to find out the Implementation of Law Number 7 of 2017 concerning General Elections Regarding the Recruitment of Legislative Candidates by Political Parties in Sukoharjo Regency and the emergence of obstacles during the implementation of the general election. This research was empirical legal research. The data were obtained from the research in Sukoharjo District including the Office of the Regional People’s Representative Council. Data collection was conducted in a field study and literature study to obtain primary data and secondary data with a qualitative descriptive method. The results of this study can be concluded that the implementation of General Elections regarding the Recruitment of Legislative Candidates by Political Parties in Sukoharjo Regency is underlain by the recruitment of legislative candidates who cannot always generate or in line with the inclination of the people. In order to guarantee and advance the welfare of the people as citizens, the political parties in Sukoharjo Regency have the role to provide political education to the public so that the public is not apathetic in every general election that is held. The obstacles that arise in the implementation are from the ineffectiveness of those political parties as well as the community in which the people argue that the political parties have yet maximally realize the inclination of the people towards the qualified and trustworthy representatives in Sukoharjo regency.